Leading change: motivational conversation can fuel effective action - Min, Li Li; Johnson, Sharon; Ziedonis, Douglas (Journal of Innovation and Healthcare Management, 2019)
The call to transform the health system is ongoing and unequivocal; to create a new standard of care delivery that is safer, lower cost, more accessible and more effective.  Innovation is required to remodel the system, not only through new technologies or pharmaceuticals, but also management actions that create better care delivery processes.  For instance, Lean thinking, a management model derived from the Toyota Production System, is a global phenomenon that has been implemented across different service and manufacturing industries, including healthcare.  Successful histories from healthcare institutions have been made public, and converted into models, for example the Mayo Clinic way and the ThedaCare Lean Management System.